Trusting on the edge : managing uncertainty and vulnerability in the midst of serious mental health problems - Brown, Patrick (Patrick R.); Calnan, Michael (Bristol : Policy, 2012)
This book explores issues central to contemporary theoretical debates around the nature of trust, linking abstract concerns to empirical analysis with interviews with service-users, practitioners and managers.
Title from publisher's bibliographic system (viewed on 01 Sep 2022).
Keywords: Trust; Mentally ill -- Psychology; Mental health facilities; Physician and patient